Manajemen Keuangan Sekolah Dalam Pemenuhan Sarana Prasarana Pendidikan di Bekasi - Adriana Hanny Bella Sukma; Alifia Maharani Nasution (STAI Terpadu Yogyakarta, 2022)
This study aims to analyze the financial management of schools in the fulfillment of educational facilities at SDN Wanasari 01, Cibitung, Bekasi. This research uses a qualitative case study approach. The data collection technique is done by using interviews, observation, and documentation. The data analysis technique uses data reduction, data display, and conclusion drawing/verification. Checking the validity of the data is done through; credibility, transferability, dependability, and confirmability. The results showed that school financial management in fulfilling educational facilities at SDN Wanasari 01 Cibitung Bekasi was carried out through school budget planning, school financial accounting, and school financial accountability.